Differential Expression Profiles and Functional Analysis of Long Non-coding RNAs in Children With Dilated Cardiomyopathy - Cai, Dongxiao; Han, Bo; Sun, Wei; Zhang, Li; Wang, Jing; Jiang, Diandong; Jia, Hailin (Frontiers in Pediatrics, 2021)
Aim: To evaluate the expression profile of long non-coding RNAs(lncRNAs) in different left ventricular function of dilated cardiomyopathy (DCM) in children and explore their possible functions. Methods: The lncRNA microarray experiment was used to determine the differential expression profile of lncRNA in 3 children with DCM and 3 healthy volunteers. The functional analysis and the construction of the lncRNA-mRNA interaction network were carried out to study the biological functions. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis was used to verify the microarray data. Results: There were 369 up-regulated lncRNAs identified in the DCM patients(fold change＞2, P＜0.05), and 505 down-regulated lncRNAs. Based on target gene prediction and co-expression network construction, 9 differentially expressed lncRNAs were selected for the PCR to verify the accuracy of the microarray data, of which 5 were up-regulated and 4 were down-regulated, and finally proved that 7 of them were consistent with the trend of microarray data results. Four of these lncRNAs had significant differences between the patients with poor cardiac function and patients with improved left ventricle function. Conclusion: LncRNAs may play an important role in pediatric DCM and may provide a new perspective for the pathogenesis, diagnosis and treatment of this disease.